双种植体-杆卡固位覆盖义齿修复下颌无牙颌的临床应用 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2017)
Implant-overdenture supported by an interforaminal bar provides stability and is effective in an edentulous atrophic mandible. However, using this attachment requires precise planning from the restorative and surgical aspects to ensure a satisfying outcome. Consdering the feature and space requirements for bar attachment, this article establishes a clinical protocol for a two-implant-retained overdenture on the mandible. In this study, a case of mandibular edentulism was considered to illustrate this protocol and provide a reference for clinical practice.